Hemodynamic consequences of a multilayer flow modulator in aortic dissection. - Athanasiou, Lambros S.; Nezami, Farhad Rikhtegar; Edelman, Elazer R. (Medical & Biological Engineering & Computing, 2019)
Aortic dissections are challenging for it remains perplexing to determine when surgical, endovascular, or medical therapies are optimal. We studied the effect of the multilayer flow modulator (MFM) device in patients with different forms of type-B aortic dissections. CT scans were performed pre-, immediately post-MFM implantation, and multiple times within a 24-month follow-up. Three-dimensional reconstructions were created from these scans and the multilayer or single-layer mesh device placed virtually into the true lumen. We observed that MFM device can sufficiently restore flow perfusion, reduce the false lumen, eliminate local flow recirculation, and reduce wall shear stress distribution globally. Single-layer devices can reduce false lumen dimensions; however, they generate local disturbance and recirculation zones in selected areas at specific time points. Moreover, in polar extremes of dissection, the MFM device restored flow to vital organs perfusing vessels independent of effects on luminal patency. Management of aortic dissections should focus on modulation of blood flow, suppression of local recirculation, and restoration of vital organ perfusion rather than primarily restoring vascular lumen morphology. While the latter restores the geometry of the true lumen, only the former restores homeostasis. Graphical abstract.